The Counter Text Interview: Stephanie Strickland. - Strickland, Stephanie; Aquilina, Mario; Callus, Ivan (CounterText, 2016)
An interview with U.S. writer Stephanie Strickland is presented. She states her interest in code, mathematics, and poetry as languages. She notes that electronic literature does not tends towards fragmentation and reading and knowledge acquisition make use of fragment in number of ways. She mentions that one cannot control proprietary obsolescing of platforms and commercial refusal to agree to common standards.